Prosedur Eksekusi Objek Lelang Hak Tanggungan Dimana Objek Masih Dikuasai Pihak Lain - Hikmah Nurul Hidayah; Siti Malikhatun Badriyah (Magister Kenotariatan Universitas Diponegoro, 2022)
Civil cases arise from a hindrance relationship in which the debtor's performance obligations and the creditor's right to performance will be without hindrance if each party fulfills its obligations. Execution is an attempt by a creditor to realize his rights by force because the debtor does not fulfill his obligations voluntarily. The definition above the purpose of writing this law is to find out how the legal protection given to the auction winner for the auction object which is still controlled by another party, along with the execution procedure and the obstacles it encounters. Procedure for legal protection that can be given to auction subjects, first the winner of the auction submits a request for vacant execution at the Semarang District Court, then the Chairperson of the Semarang District Court gives Aanmaning to carry out voluntary vacating, if it has not been heeded then Aanmaning will be carried out again so that he will be executed heeding the warning from the Chairman Semarang District Court, then if the person executed continues to control the auction item, the Chief Justice will order a bailiff to vacate.Keywords: Execution; Auction; Civil CasesAbstrakPerkara perdata timbul dari suatu hubungan perintangan dimana debitur memiliki memiiki kewajiban untuk mendapatkan prestasi dan kreditur berhak terhadap prestasi, akan tanpa hambatan jika seluruh pihak melakukan pemenuhan kewajiban yang mengenainya. Eksekusi menjadi usaha kreditor menjadikan hak secara paksa menjadi nyata sebab kewajiban yang tidak dapat dipenuhi oleh debitor secara sukarela. Definisi diatas tujuan penulisan hukum ini adalah guna melihat bagaimana pemenang lelang dilindungi oleh hukum atas objek lelang yang masih dikuasai pihak lain, berikut prosedur eksekusinya serta hambatan-hambatan yang ditemuinya. Prosedur Perlindungan hukum yang dapat diperoleh subjek lelang, terlebih dahulu pemenang lelang melakukan pengajuan di Pengadilan Negeri Semarang terkait permohonan eksekusi pengosongan, kemudian Ketua Pengadilan Negeri Semarang memberikan Aanmaning untuk melakukan pengosongan secara sukarela, bilamana belum diindahkan maka akan dilakukan Aanmaning lagi supaya tereksekusi mengindahkan teguran dari Ketua Pengadilan Negeri Semarang, maka bila tereksekusi masih terus menguasai barang lelang Ketua Pengadilan akan memerintahkan seorang juru sita untuk melakukan pengosongan.Kata Kunci : Ekskusi; Lelang; Perkara Perdata